Elementary School Teachers’ Strategies in Enhancing Students’ Interest in Social Studies - Safiuddin; Risman Iye; Karim (Jurnal Wawasan Sarjana, 2025)
Social studies education in elementary schools plays a crucial role in developing students’ understanding of society, culture, and civic responsibility. However, low student engagement and limited interest in the subject often hinder effective learning. This study aims to explore strategies employed by elementary school teachers to enhance students’ interest in social studies, focusing on interactive learning, integration of local context and culture, use of creative learning media, and collaboration with parents and the community. A qualitative research design was adopted, employing classroom observations, semi-structured interviews, and document analysis of lesson plans and teaching materials. Purposive sampling was used to select teachers who implement innovative and student-centered approaches in their classrooms. The findings reveal that interactive strategies such as group discussions, role-playing, and simulations increase student participation and motivation. Lessons connected to local culture and community issues make content more relevant and meaningful, while creative media and project-based tasks enhance comprehension and active learning. Collaboration with parents and the community further strengthens engagement and fosters social awareness, empathy, and civic responsibility. These strategies collectively contribute to improved academic outcomes, positive attitudes toward learning, and the development of critical thinking and social skills. The study underscores the vital role of teachers as facilitators who link students to knowledge, culture, and society.